Levels of Cd (II), Mn (II), Pb (II), Cu (II), and Zn (II) in Common Buzzard (Buteo buteo) from Sicily (Italy) by Derivative Stripping Potentiometry. (3rd May 2010) - Licata, P.; Naccari, F.; Lo Turco, V.; Rando, R.; Di Bella, G.; Dugo, G.
Abstract : The purpose of this study was to determine the concentrations of heavy metals (Cd, Pb, Cu, Mn, and Zn) in different organs (liver, kidney, muscle, lung, skin, and feathers) of buzzards ( Buteo buteo ), utilized as a "biological indicator" for environmental contamination, from different areas of Sicily and to investigate the relationships between birds sex, age, and weight and metal levels in these samples. All samples of common buzzards were collected at the "Recovery Center of Wild Fauna" of Palermo, through the Zooprophilactic Institute. Potentiometric stripping analysis (PSA) was used to determine the content of Cd(II), Cu(II), Mn(II), Pb(II), and Zn(II) in bird tissues. For toxic metals, the highest levels of Pb were in liver and those of Cd in lung; Zn levels were higher than Cu and Mn in all tissues analyzed. The concentrations in liver, lung, kidney, and muscle could be considered as an indicative of chronic exposure to metals while the presence of metals in skin could be consequential to storing and elimination processes. The found concentrations of metals in the studied matrices required a highly sensitive method for their determination and a simple sample preparation procedure, and the proposed method was well suited for this purpose.